Evolution of NLR Resistance Genes in Magnoliids: Dramatic Expansions of CNLs and Multiple Losses of TNLs - Wu, Jia-Yi; Xue, Jia-Yu; Van de Peer, Yves (Frontiers in Plant Science, 2021)
Magnoliids are the third-largest group of angiosperms and occupy a critical position in angiosperm evolution. In the past years, due to the lack of sequenced genomes, the disease resistance gene (R gene) profile of magnoliids remains poorly understood. By the genome-wide identification of 1,832 NLR genes from seven magnoliid genomes, we built a framework for the evolution of magnoliid R genes. TNL genes were completely absent from five magnoliids, presumably due to immune pathway deficiencies. A total of 74 ancestral R genes (70 CNLs, 3 TNLs, and 1 RNL) were recovered in a common ancestor of magnoliids, from which all current NLR gene repertoires were derived. Tandem duplication served as the major drive for NLR genes expansion in seven magnoliid genomes, as most surveyed angiosperms. Due to recent rapid expansions, most magnoliids exhibited “a first expansion followed by a slight contraction and a further stronger expansion” evolutionary pattern, while both Litsea cubeba and Persea americana showed a two-times-repeated pattern of “expansion followed by contraction.” The transcriptome analysis of seven different tissues of Saururus chinensis revealed a low expression of most NLR genes, with some R genes displaying a relatively higher expression in roots and fruits. Overall, our study sheds light on the evolution of NLR genes in magnoliids, compensates for insufficiency in major angiosperm lineages, and provides an important reference for a better understanding of angiosperm NLR genes.